The outcome of patients with advanced pure squamous or mixed squamous and transitional urothelial carcinomas following platinum-based chemotherapy - Kastritis, E.; Dimopoulos, M.-A.; Antoniou, N.; Deliveliotis, C.; Chrisofos, M.; Skolarikos, A.; Gika, D.; Bamias, A. (Anticancer Research, 2006)
Background: There is limited information about the benefit from systemic chemotherapy in non-pure Transitional Cell Carcinomas (TCCs) of the urothelial tract. In this study the efficacy of platinum-based chemotherapy in patients with pure squamous or mixed carcinomas was retrospectively analysed and compared with that in pure TCCs. Patients and Methods: Analysis included 446 consecutive patients treated with platinum-based chemotherapy for advanced or metastatic urothelial cancer. There were 389 (87%) patients with pure TCC, 15 (3.5%) with pure Squamous Cell Carcinomas (SCC) and 42 (9.5%) patients had mixed histology (TCC+SCC) tumors. Results: There were no statistically significant differences in baseline characteristics (gender, PS, haemoglobin, sites of metastases) although disease in the pelvis was more frequent in mixed tumors than in pure TCCs (46% vs. 30%, p=0.034). Median survival for patients with TCC histology was 11.3 months, for SCC patients 13.6 months and 10.4 months for patients with mixed histology (p=0.720). Response rates were 44% for patients with TCC, 27% for patients with SCC and 34% for mixed histology patients (p=0.210). Multivariate analysis showed that presence of visceral metastases and poor performance status, were associated with worse prognosis in mixed histology tumors. Conclusion: Non-transitional histology does not predict for an inferior survival after platinum-based chemotherapy for advanced urothelial carcinoma. Well-known prognostic factors in transitional cell carcinomas were also associated with prognosis in mixed carcinomas.
Keywords: Bladder cancer; Carboplatin; Metastatic; Mixed tumors; Non-urothelial; Platinum; Squamous; Urothelial